Less is More in Hong Kong: Investigation of Biscriptal and Trilingual Development Among Chinese Twins in a (Relatively) Small City. (5th December 2016) - Wong, Simpson W. L.; Ho, Connie Suk-Han; McBride, Catherine; Chow, Bonnie Wing-Yin; Waye, Mary Miu Yee
Abstract : One salient characteristic of twin studies and the related behavioral genetics paradigm is the requirement of a large sample size. Countries or regions that are large in size and highly populated are at an advantage when implementing twin studies. However, given the fascinating and promising results obtained from twin studies, many researchers based in smaller countries or regions may still want to conduct twin studies in order to address local and theoretical issues. In this article, we have outlined the development of twin studies in Hong Kong, one of the Special Administrative Regions of China. The historical development and design of the two major twin studies of language and reading development implemented within Hong Kong are discussed, providing insights to researchers who also aspire to conduct twin studies in small regions.